Speech outcomes in children with cleft and palate: Srinagarind Hospital, Khon Kaen University, Thailand - N. Ooppanasak (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND| 2019. Background: Speech defects in children with cleft lip and palate are common after cleft repair. Investigation of speech outcomes provides useful information for further intervention planning and protocol reviewing. Objective: The aim of the present study was to determine speech outcomes in children with CLP, compared to normal children between 6 and 13. Materials and Methods: This was a cross-sectional study. Fifteen children with cleft palate, with or without cleft lip (CLP) and 15 normal children between 6 and 13 were enrolled. Perceptual assessment via Thai Speech Parameters for Patients with Cleft Palate in a Universal Reporting System for identification and classification speech outcomes was performed by two senior speech and language pathologists by consensus. Descriptive analysis and Wilcoxon Sign Rank Test were used to present the data. Results: The prevalence of speech abnormalities in primary school-aged children with CLP was high (viz., articulation errors (100%), abnormalities of resonance (hypernasality: 44%), audible nasal emission/turbulence (44 to 60%), voice disorders (27%), intelligibility (36%), less understandability (60%), deviation acceptability (87%). Children with CLP had more speech abnormalities of both types and numbers than normal children (median difference = 9; 95% confident interval = 7, 10). Conclusion: Speech abnormalities in primary school-aged children with CLP were common, including: CAD, hypernasality, voice disorders, audible nasal emission/turbulence, less understandability, and deviation acceptability.